SYNTHESIS, CHARACTERIZATION, MOLECULAR DOCKING, ADMET PROPERTIES AND IN-VITRO ANTI-INFLAMMATORY SCREENING OF SOME ISOXAZOLINE DERIVATIVES (Indian Journal of Chemistry (IJC), 2024)
This paper describes the synthesis of isoxazoline derivatives using Bi2O3-TiO2 nanocatalyst. The (E)-3-(2-amino-3,5-dibromophenyl)-1-(substituedphenyl)prop-2-en-1-one were treated with hydroxylamine hydrochloride in the presence of nanocatalyst Bi2O3-TiO2 and ethanol as solvent to yield 2,4-dibromo-6-(3-(substitutedphenyl)-4,5-dihydroisoxazol-5-yl)aniline (8-14). The final product separated and purified by ethanol recrystallization. The obtained final product (8-14) was characterized by elemental analysis, FT-IR, 1HNMR and 13CNMR spectral studies. Synthetic transformation details, smallest catalytic amounts, excellent product yields, and suitable solvent for the formation of these isoxazoline scaffolds are elucidated. Synthesized derivatives screened for their in-vitro anti-inflammatory activity using HRBC method. The obtained in vitro results were compared with the molecular docking with protein, DNA Gyrase (PDB ID: 3U2D), Cyclooxygenase-1 (PDB ID: 3N8V) and Cyclooxygenase-2 (PDB ID: 3LN1) enzyme using Schrodinger suit Maestro 11.2 version. Insilico ADMET screening also performed by qikprop module of Schrodinger suit.